Consider y = mx + c as the line passing through the point (-1, 2)

So we get

2 = m (-1) + c

By further calculation

2 = -m + c

c = m + 2

Substituting the value of c

y = mx + m + 2 …… (1)

So the given line is

x + y = 4 ……. (2)

By solving both the equations we get

\( x=\dfrac{2-m}{m+1}\) and \( y=\dfrac{5m+2}{m+1}\)

\( \dfrac{2-m}{m+1},\dfrac{5m+2}{m+1}\) is the point of intersection of lines (1) and (2) .

Given that, the point is at a distance of 3 units from (-1,2)

By distance formula,

\(\sqrt{ (\dfrac{2-m}{m+1}+1)^2+(\dfrac{5m+2}{m+1}-2)^2}=3\)

Square both sides,

\( (\dfrac{2-m+m+1}{m+1})^2+(\dfrac{5m+2-2m-2}{m+1})^2=3^2\)

= \( \dfrac{9}{(m+1)^2}+\dfrac{9m^2}{(m+1)^2}=9\)

Divide the equation by 9 ,

\( \dfrac{1+m^2}{(m+1)^2}=1\)

By cross multiplication

1 + m^{2} = m^{2} + 1 + 2m

So we get

2m = 0

m = 0

Therefore, the slope of the required line must be zero that is, the line must be parallel to the x-axis.

Answered by Pragya Singh | 1 year agoFind the angle between the line joining the points (2, 0), (0, 3) and the line x + y = 1.

Prove that the points (2, -1), (0, 2), (2, 3) and (4, 0) are the coordinates of the vertices of a parallelogram and find the angle between its diagonals.

Find the acute angle between the lines 2x – y + 3 = 0 and x + y + 2 = 0.

Find the angles between pairs of straight lines 3x – y + 5 = 0 and x – 3y + 1 = 0

Find the angles between pairs of straight lines 3x + y + 12 = 0 and x + 2y – 1 = 0